Deliberative research as a tool to make value judgements. (June 2014) - Burchardt, Tania
The purpose of deliberation as a research technique (as opposed to policymaking or public consultation) is distinctive: to uncover the public's informed, considered and collective view on a normative question. Such questions often arise in relation to research on poverty and inequality, where there is a need to justify the thresholds and concepts adopted on a deeper basis than convention alone can offer. But can deliberative research provide the answer, and if so in what circumstances? By comparing deliberative research to more traditional methods, such as in-depth interviewing, attitudinal surveys, ethnography and participatory approaches, this article reveals that deliberative designs involve a number of assumptions, including a strong fact/value distinction, an emphasis on 'outsider' expertise and a view of participants as essentially similar to each other rather than defined by socio-demographic differences. Using an example of deliberative research in which the author was involved, developing a list of 'capabilities' for monitoring inequalities in Britain, it also demonstrates that normative decisions permeate the design and implementation of deliberative research in practice. Thus, while deliberative research has the potential to provide uniquely considered, insightful and well-justified answers to the problem of defining a collective position on key questions in social science, it is currently under-theorised as an approach, and transparency at all stages of the process is essential to avoid the charge of simply reflecting the researchers' implicit values.